2004
DOI: 10.1111/j.1467-9701.2004.00669.x
|View full text |Cite
|
Sign up to set email alerts
|

FDI and Industrial Restructuring in Post‐WTO Greater PRD: Implications on Regional Growth in China

Abstract: This paper aims at studying the investment flows in the Greater Pearl River Delta region (Hong Kong‐PRD) in China and its impacts on industrial restructuring at the firm‐level using a business survey with the Hong Kong‐PRD entity acted as a core‐periphery economy. The critical effects of gravity distance on transaction costs in the determination of investment flows are examined statistically by a gravity model by incorporating a hypothetical infrastructural construction project. Survey findings show that the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…That is, Hong Kong is basically service-oriented and the labour-intensive manufacturing sector is located across Hong Kong's border (Tuan and Ng, 2001b). Tuan and Ng (2002) suggested that the FDI-induced agglomeration of Hong Kong and the Pearl River Delta (PRD) will provide invaluable experience which will lead to further agglomeration, especially in regions such as the Shanghai-Yangtze River Delta (YRD) and the BeijingBohai Gulf (Tuan and Ng, 2004).…”
Section: Foreign Direct Investment and The Effect On Human Capital Fomentioning
confidence: 99%
“…That is, Hong Kong is basically service-oriented and the labour-intensive manufacturing sector is located across Hong Kong's border (Tuan and Ng, 2001b). Tuan and Ng (2002) suggested that the FDI-induced agglomeration of Hong Kong and the Pearl River Delta (PRD) will provide invaluable experience which will lead to further agglomeration, especially in regions such as the Shanghai-Yangtze River Delta (YRD) and the BeijingBohai Gulf (Tuan and Ng, 2004).…”
Section: Foreign Direct Investment and The Effect On Human Capital Fomentioning
confidence: 99%
“…Suffering from poor domestic market access, industrial enterprises in the PRD heavily rely on international markets. With the support of migrants and foreign investments, especially those from Hong Kong and Taiwan, the PRD has become a key part of the world factory, characterized by the specialized manufacturing towns and cities (Eng 1997;Tuan and Ng 2004;Yang and Liao 2010). However, over-agglomeration of industries in PRD cities has triggered fierce competition in land, energy and infrastructure and has seriously degraded the environment.…”
Section: Regional Differences In Agglomeration Effectsmentioning
confidence: 98%
“…The PRD thus provided an ideal place for Hong Kong investors to transfer their manufacturing activities (Sit 1998; Leung 1996). Subcontracting activities from Hong Kong were widely distributed in the PRD, stimulating unprecedented economic growth (Leung 1993; Tuan & Ng 2004).…”
Section: Economic Growth and Spatial Restructuring In The Prdmentioning
confidence: 99%
“…Since the 1980s, industrial development has been encouraged and accelerated by a series of economic reforms which aimed to promote exportoriented manufacturing. The past three decades have witnessed profound industrial growth, transforming the PRD from an agricultural region to China's leading manufacturing centre, a gateway to China for international trade (Sit and Yang 1997;Tuan and Ng 2004;Chen 2007) and one of the fastest growing regions in the world (Enright et al 2005). Two of the nine municipalities have been the economic centres in the PRD -Guangzhou the provincial capital and Shenzhen the first special economic zone (SEZ) in China.…”
Section: Economic Growth and Spatial Restructuring In The Prdmentioning
confidence: 99%